2019
DOI: 10.1136/rapm-2018-100366
|View full text |Cite
|
Sign up to set email alerts
|

Trends in steroid agent and diluent choices for epidural steroid injections: a survey of Spine Intervention Society physicians

Abstract: BackgroundEpidural steroid injections (ESIs) are a frequently used treatment for refractory radicular spinal pain. ESIs, particularly transforaminal epidural steroid injections (TFESI), may provide pain relief and delay the need for surgery. Corticosteroid agent and diluent choices are known to impact the safety of ESIs. In particular, the risk of embolization with particulate corticosteroids has led to recommendations for non-particulate steroid use by the Multisociety Pain Workgroup. Additionally, there is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Because of the risk of accidental intravascular injection and consequent neurological injuries, non-particulate steroids have been recommended, instead of a particulate steroid, in recent years. Clements et al [26] designed a cross-sectional survey study composed of 314 physicians, who were members of the Spine Interventional Society, and approximately 41% reported using particulate steroids for lumbar TFESI, and 74% for lumbar ILESI, indicating the variability in clinical practice. Chatterjee et al [27] reported that using methylprednisolone, a particulate steroid, provides significantly longer pain relief than dexamethasone, a non-particulate steroid.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the risk of accidental intravascular injection and consequent neurological injuries, non-particulate steroids have been recommended, instead of a particulate steroid, in recent years. Clements et al [26] designed a cross-sectional survey study composed of 314 physicians, who were members of the Spine Interventional Society, and approximately 41% reported using particulate steroids for lumbar TFESI, and 74% for lumbar ILESI, indicating the variability in clinical practice. Chatterjee et al [27] reported that using methylprednisolone, a particulate steroid, provides significantly longer pain relief than dexamethasone, a non-particulate steroid.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are consensus and recommendations from the regulatory bodies or professional organisations, current practice in choosing steroids and diluents for epidural injection varies considerably between workgroups and centres. A recent study showed that 41% and 9% of physicians still use particulate steroids for lumbar and cervical transforaminal epidural injections, respectively . The choice of steroids and diluents may indeed influence safety.…”
Section: Continuing Usementioning
confidence: 99%
“…Moreover, one of the aims of diluting steroids with local anaesthetics is to provide immediate pain relief for diagnostic purposes . The local anaesthetic can also help to reduce the discomfort or pain arising from the pressure or volume effects on the sensitive tissues inside the spinal cord . Corticosteroid preparations may also contain excipients such as polyethylene glycol (a drug vehicle) or benzyl alcohol (a preservative) that can be toxic .…”
Section: Dilutionmentioning
confidence: 99%
“…In terms of efficacy, there has been conflicting data in the literature regarding the use of particulate versus non-particulate steroids for ESI [4][5][6][7]. A recent survey of spine interventionalists demonstrated considerable variability with respect to choice of steroid for transforaminal ESI, underscoring the significant difference of opinion and level of comfort that still exists regarding utilization of these agents [8].…”
Section: Medication Choicementioning
confidence: 99%